2005
DOI: 10.1177/0093650205281056
|View full text |Cite
|
Sign up to set email alerts
|

Organizing for Information Retrieval in Transactive Memory Systems

Abstract: Advancing transactive memory (TM) theory, this research explores information retrieval between members of 12 preexisting organizational work teams. The teams examined are larger than the ad hoc groups studied in previousTM research. The central components are team members' (a) communication for topic-specific information retrieval, (b) perceptions of their own knowledge levels, and (c) perceptions of each others' knowledge levels. Social network analysis techniques were used to examine the communication ties b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 29 publications
(55 reference statements)
1
90
0
3
Order By: Relevance
“…Like maximum pseudo-likelihood p* modelling (Wasserman and Pattison, 1996;Palazzolo, 2005;Contractor et al, 2006), ERGM examines the probability of certain network configurations, or sub graphs, within the larger network. The benefit of Monte Carlo maximum likelihood estimations is that it most closely suits the interdependency of network observations and has been shown to produce more reliable estimates than pseudo-likelihood p* modelling Robins et al, 1999;Lubbers and Snijders, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like maximum pseudo-likelihood p* modelling (Wasserman and Pattison, 1996;Palazzolo, 2005;Contractor et al, 2006), ERGM examines the probability of certain network configurations, or sub graphs, within the larger network. The benefit of Monte Carlo maximum likelihood estimations is that it most closely suits the interdependency of network observations and has been shown to produce more reliable estimates than pseudo-likelihood p* modelling Robins et al, 1999;Lubbers and Snijders, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using an online survey, called the Knowledge Asset Mapping Exercise (KAME; Palazzolo, 2005;Yuan et al, 2005). The KAME instrument was customised for this team based on ethnographic (Ibrahim and Paulson, 2008) and computational modelling research (Ibrahim and Nissen, 2007) and additional consultation with the project manager.…”
Section: Knowledge Asset Mapping Exercise Proceduresmentioning
confidence: 99%
“…The survey, which was inspired by the Knowledge Asset Mapping Exercise in Palazzolo (2005) and structured according to the format proposed by Wasserman and Faust (1994) for network data collection, included questions about respondent attributes (i.e., gender, years of experience, affiliations with formal groups) and advice seeking relationships with other pediatricians in the respective LHA (a roster was used with all of the pediatricians' names listed in the survey). The following question was asked to physicians to collect advice ties data: "Suppose that you are confronted with a clinical problem that is affecting one of your patients, for which you cannot find a solution yourself.…”
Section: Empirical Settingmentioning
confidence: 99%
“…Understanding perceptions of signals is important since research has shown that perceptions of expertise is more influential than actual expertise in expertise seeking [31].…”
Section: Studymentioning
confidence: 99%